(RETRACTION) KAJIAN ETNOSEMANTIK: KESEPADANAN MAKNA PERIBAHASA BERSUMBER NAMA BINATANG DALAM BAHASA INDONESIA DAN BERBAGAI BAHASA DAERAH - Maulina Hendrik (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2018)
RETRACTIONRETRACTION TO: Hendrik,M. (2018). KAJIAN ETNOSEMANTIK: KESEPADANAN MAKNA PERIBAHASA BERSUMBER NAMA BINATANG DALAM BAHASA INDONESIA DAN BERBAGAI BAHASA DAERAH. Dialektika : Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 5(1), 102-119. doi:10.15408/dialektika.v5i1.7103.  This article has been retracted by Publisher based on the following reason:The Editor of dialektika Journal found the double publication in the article publishing due to article's content similarity published in Prosiding KIMLI 2014, cet. 1 ISBN 978-602-17161-1-3. Titled” Kesepadanan Makna Peribahasa Bersumber Nama Binatang dalam Bahasa Indonesia dan Berbagai Bahasa Daerah (Suatu Kajian Etnosematik)” with the author who is Euis Nicky Marnianti Suhendar. Based on clarification, Author of the article have admitted that he has published the article published in  Prosiding KIMLI 2014, cet. 1 ISBN 978-602-17161-1-3, URL: https://lib.atmajaya.ac.id/default.aspx?tabID=61&id=278122&src=a.One of the conditions of submission of paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.